2011
DOI: 10.1002/anie.201008224
|View full text |Cite
|
Sign up to set email alerts
|

Encapsulation of Nanoparticles in Block Copolymer Micellar Aggregates by Directed Supramolecular Assembly

Abstract: Worm holes: Cylindrical or wormlike block copolymer micelles with gold nanoparticles encapsulated in a micellar core were fabricated through directed supramolecular assembly. This versatile approach allows fine‐tuning of interparticle spacing and micellar morphology by varying the content of the nanoparticles or hydrogen bonding agent in the supramolecular assemblies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
129
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 112 publications
(135 citation statements)
references
References 31 publications
4
129
2
Order By: Relevance
“…1−5 Up to now, a number of strategies have been developed to fabricate the hybrid BCPs/NPs nanomaterials, including coprecipitation method, 6,7 heating−cooling processing, 8 electrostatic interaction approach, 9 directed supramolecular assembly, 10 interfacial instabilities of emulsion droplets, 11,12 and so forth. On the other hand, it has been reported that the neat BCPs can self-assemble into unique microphaseseparated nanostructures confined in emulsion droplets because the confinement effect can effectively break the symmetry of the structure, thus resulting in the nanostructures that are not available in the free systems.…”
Section: Introductionmentioning
confidence: 99%
“…1−5 Up to now, a number of strategies have been developed to fabricate the hybrid BCPs/NPs nanomaterials, including coprecipitation method, 6,7 heating−cooling processing, 8 electrostatic interaction approach, 9 directed supramolecular assembly, 10 interfacial instabilities of emulsion droplets, 11,12 and so forth. On the other hand, it has been reported that the neat BCPs can self-assemble into unique microphaseseparated nanostructures confined in emulsion droplets because the confinement effect can effectively break the symmetry of the structure, thus resulting in the nanostructures that are not available in the free systems.…”
Section: Introductionmentioning
confidence: 99%
“…Micelles are used in diverse fields including drug delivery, oil recovery, extraction etc, and to control order or porosity in inorganic materials 6,7 . Due to their colloidal size, they undergo random Brownian motion in liquids.…”
mentioning
confidence: 99%
“…The cationic segment is normally composed of pyridine or amino groups which are readily protonated under acid condition and thus can interact with anionic POMs through electrostatic force. Based on this method, a series of POM clusters including [SiMo 12 9− have been coassembled with BCPs, which leads to various hybrid assemblies such as spherical micelles, worm-like micelles, vesicles, and nanostructured inverse hexagonal films. 31−35 Although the electrostatic assembly method has made fruitful progresses, it is only suitable for special BCPs containing cationic segments; besides, a certain pH value is required to maintain the positively charged state of polymer segment, which may change the structure of some unstable POMs.…”
Section: Introductionmentioning
confidence: 99%